A NOVEL SPECTROPHOTOMETRIC METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF TENOFOVIR DISOPROXIL FUMERATE USING HYDROTROPIC SOLVENTS. (International Journal of Food and Nutritional Sciences, 2022)
Ultraviolet-Visible spectrophotometric method for estimation of poorly water soluble drug like Tenofovir Disproxil Fumerate, has been developed. Aqueous solubility of drug has been enhanced to great extent (15folds) in 10%Urea + 30% Sodium benzoate blend. The primary objective of the present investigation was to employ these hydrotropic solutions to extract the drugs from their dosage forms, precluding the usage of costlier organic solvents. The selected λmax 300nm, Urea and Sodium benzoate did not show any interference during estimation. The results of analysis have been validated statistically according to ICH guidelines, and by recovery studies. The proposed methods are new, simple, easy, economic, co-friendly, accurate, safe and precise.Key Words; Tenofovir Disproxil Fumerate, Urea, Sodium Benzoate, Hydrotrophic, ICH Guidelines,